2022
DOI: 10.1080/15592324.2021.1994248
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression pattern analysis of the TCP transcription factor family in Ginkgo biloba

Abstract: Plant-specific TCP transcription factors play an essential role in plant growth and development. They can regulate leaf curvature, flower symmetry and the synthesis of secondary metabolites. The flavonoids in Ginkgo biloba leaf are one of the main medicinally bioactivate compounds, which have pharmacological and beneficial health effects for humans. In this study, a total of 13 TCP genes were identified in G. biloba , and 5 of them belonged t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Besides Arabidopsis , TCPs were characterized in several land plants, as rice, tomato, soybean, cotton, chrysanthemum, peach, apple, Setaria italica and Setaria viridis [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], among others. In addition, genome-wide analysis allowed the identification of TCP genes in numerous species of commercial interest, as tobacco, banana, Brassica napus , cucumber, watermelon, strawberry, eggplant, Ginkgo biloba , and tea [ 22 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. For the interested reader, an exhaustive analysis of the phylogeny and the evolution of the TCP family in 37 plant species from lower to higher plants was recently reported by Zhou et al [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides Arabidopsis , TCPs were characterized in several land plants, as rice, tomato, soybean, cotton, chrysanthemum, peach, apple, Setaria italica and Setaria viridis [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], among others. In addition, genome-wide analysis allowed the identification of TCP genes in numerous species of commercial interest, as tobacco, banana, Brassica napus , cucumber, watermelon, strawberry, eggplant, Ginkgo biloba , and tea [ 22 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. For the interested reader, an exhaustive analysis of the phylogeny and the evolution of the TCP family in 37 plant species from lower to higher plants was recently reported by Zhou et al [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the roles of TCP members in UV-B- and MeJA-mediated TIA biosynthesis are largely unknown. In Ginkgo biloba , the expression of GbTCP06 , GbTCP11 , and GbTCP13 was significantly up-regulated by exogenous of MeJA application ( Yu et al., 2022b ). In Chinese flowering cabbage, BrTCP7 is associated with MeJA-mediated leaf senescence by activating JA signaling pathway and chlorophyll metabolism ( Xu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that TCP family played essential roles in secondary metabolism. In Ginkgo biloba , three TCP family members, such as GbTCP03 , GbTCP04 , and GbTCP07 , were reportedly involved in flavonoid biosynthesis ( Yu et al., 2022b ). Heterologous overexpression of GbTCP5 gene in Arabidopsis increased the lignin biosynthesis by binding to TCP II type cis -acting elements ( Wang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows the protein ML phylogenetic tree, our analyses concurred with previous findings that the TCP gene family can be divided into three main groups: the PCF, CIN, and the CYC/TB1 ( Citerne et al, 2003 ). Likewise, the Bayesian inference methods have sorted TCP sequences in groups of high similarity, the class I (PCF1/2 clade) and class II (CIN and CYC/TB1) ( Manassero et al, 2013 ; Liu et al, 2019 ; Yu L. et al, 2022 ). Nonetheless, distinctions have not been made whether the class I or class II TCP subfamily was the first to appear in plant kingdom due to the fact that lower plants believed to be first forms of plant life like Marchantia polymorpha carry both classes ( Sharma et al, 2013 ).…”
Section: Phylogenetics and Evolution In Tcp Gene Familymentioning
confidence: 99%
“…Although their ancestry remains unknown ( Navaud et al, 2007 ), their biological roles and mode of action are conserved in plant species from the bryophytes to the angiosperms. Up to date, there have been several breakthroughs in the identification and computation of TCP TFs in numerous plant species including: A. thaliana ( Aggarwal et al, 2010 ), G. biloba ( Yu L. et al, 2022 ), P. edulis ( Liu et al, 2018 ), S. lycopersicum ( Parapunova et al, 2014 ), L. chinense ( Hwarari et al, 2022 ), etc. However, in some plant orders, the TCP TFs have not yet been identified ( Manassero et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%